The Impact of Application of Android Mobile Application-Based Online Credit as an Effort to Accelerate Credit Disbursement: Dampak Penerapan Pemberian Kredit Online Berbasis Aplikasi Mobile Android sebagai Upaya Percepatan Pencairan Kredit - Mifta Salwa; Fityan Izzah Noor Abidin (Academia Open, 2021)
This study aims to determine the positive and negative impacts of the application of online credit distribution based on the android mobile application as an effort to accelerate credit disbursement in the Tunaiku application. To obtain the data needed in the study, the researcher tries to obtain related data such as primary data, which is sure that the data obtained by a researcher is directly from the object. In this study, the primary data source came from the results of interviews with the Tunaiku application and the second party who was the debtor of the Tunaiku application. And secondary data, namely data obtained by a researcher indirectly from the object. In this study, the secondary data sources came from literature studies conducted by researchers. And the type of research used in this research is descriptive research with a qualitative approach. And the results of this study are the researchers found a positive impact arising from the application of online credit provision based on the Android mobile application as an effort to accelerate credit disbursement on the Tunaiku application, namely: saving time and energy, not requiring collateral for goods or other valuable documents, can be a solution for debtors who need instant funds and fast disbursement of funds, loan funds can be used for various needs, flexible ceiling amounts and tenors. And the negative impact of the application of online credit application based on the android mobile application as an effort to accelerate credit disbursement on the Tunaiku application, namely: creating a culture of debt, high interest on debt, fishing for the system to dig holes and cover holes, misuse of personal data, family or closest relatives will be disturbed.